Simultaneous medullary thyroid carcinoma and primary non-small cell lung cancer: case report and literature review - Zhang Jianyong; An Xiaoxiao; Zheng Yu; Peng Yunsong (Discover Oncology)
Abstract Medullary thyroid carcinoma (MTC) is a rare neuroendocrine tumor, accounting for 1–2% of all thyroid cancers. MTC originates from the C cells or parafollicular cells, which produce and release two critical hormones called calcitonin (CT) and carcinoembryonic antigen (CEA), both serving as key tumor markers. Elevated basal serum calcitonin is critical for diagnosing lateral neck lymph node metastasis, with levels exceeding 500 pg/mL indicating distant metastasis. Persistently elevated postoperative calcitonin levels are associated with poorer prognosis. Surgical intervention remains the only curative treatment for MTC, though local metastasis is present in 50% of cases, and distant metastasis in 10–15%, commonly affecting the lungs, liver, and bones. When pulmonary nodules are detected in MTC patients, distinguishing whether they are metastatic is crucial. Here, we present a rare case of MTC accompanied by primary non-small cell lung cancer. A 55-year-old male patient presenting with cough and sputum was diagnosed with lung nodule measuring approximately 1.8 *1.5 cm and thyroid nodules via computed tomography (CT) examination. The right thyroid nodule was diagnosed as MTC based on fine needle aspiration (FNA) and calcitonin. In addition, pulmonary nodule was evaluated as the potential for malignant tumor and lung metastasis originating from MTC by thoracic surgeons and oncologists. Due to the difficulty of percutaneous biopsy, a thoracoscopic segmentectomy was performed. Intraoperative frozen section analysis revealed that the pulmonary nodules were non-small cell lung cancer, ruling out metastasis from MTC. Subsequently, the patient underwent a radical surgery for thyroid carcinoma, and follow-up showed no recurrence based on ultrasound and lab tests. We also review clinical findings from similar cases and discuss possible treatment strategies.